Influence of Work from Home Policies and Allowances Performance on the Quality of Public Services - Iwan Kurniawan Subagja; Azis Hakim (International Journal of Social Science and Business, 2023)
Good public services must be carried out in order to create comfort, but based on monitoring in Bantargadung District, Sukabumi Regency, West Java, it is known that the quality of public services provided has not been in line with expectations during the Covid-19 virus pandemic. The purpose of this study was to determine the effect of work-from-home policies and employee performance allowances individually and jointly on the quality of public services in Bantargadung District, Sukabumi Regency, West Java. The research method with a quantitative approach. The sampling technique uses Simple Random Sampling. The number of research samples is 38 respondents. The results of the study are: a) work from home policies affect the quality of public services. b) performance allowances affect the quality of public services. c) work from home policies and performance allowances affect the quality of public services. The work from home policy in Bantargadung District, Sukabumi Regency, West Java, needs to be implemented because it has an impact on low costs, flexibility in work, increased work productivity, increased job satisfaction, the balance of work and life, and avoids disruption to the work environment, so that the implementation of this policy is expected to remain can improve the quality of public services. Performance allowances in Bantargadung District, Sukabumi Regency, West Java, need to be increased, such as the amount of salary, providing incentives, providing insurance, and providing facilities that support work activities, so that with these improvements it is expected to improve the quality of public services.